Levantamento de curvas de eficiência de aerogeradores de 3m de diâmetro utilizando modelos de turbulência RANS de uma e duas equações com comparação experimental - Carneiro, Francisco Olimpio Moura (2011)
A survey was conducted, consisting of efficiency curves applying RANS turbulence numerical models of one and two equations for a wind turbine with a diameter of 3m, using blades designed to operate under different λ with NACA 0012, 4412 and 6412 profiles. The parameterization of the mesh geometry to the size of the rotor, together with the parameterization of the refinement level compared to the ability of RANS models reached independence from the grid to the solution. Later, a numerical analysis was performed to compare the best result – a blade designed to operate under λ = 6 with the NACA 6412 profile - against experimental data. The experimental apparatus was able to collect data rotation and torque of the rotor simultaneously with the measurement of wind velocity, which obtained a maximum efficiency of approximately 25% and an operating range limited to λ = 6. It can be concluded that the models provide good accuracy in predicting the operating range of λ, however the values of Cp were underestimated. The k-ω SST model showed the best results among all.